Effects of variation of centres on the torsional analysis of asymmetrical buildings - Siddiqui, Muhammed Masihuddin; Krishna, N. Murali (Journal of Structural Engineering, 2024)
Presence of torsion makes the structural design of irregular buildings more complex and is prone to more severe damage. According to IS-1893:2016, a building is said to be torsionally irregular when the ratio of maximum horizontal displacement at any floor in the direction of lateral force to the minimum horizontal displacement at far end is more than 1.5. The torsional forces acting on a building are influenced by the relative location of the centre of mass, the centre of strength and the centre of stiffness. Therefore, these centres of significance shall be located aptly to minimise torsional effects on buildings to ensure efficient building structure. In this paper, the effects of strength eccentricity and stiffness eccentricity with respect to the centre of mass of the building are evaluated and non-linear dynamic analysis is carried-out to study the variation on torsional irregularity ratio and other torsional parameters. For the building structure, the structural configuration together with the sizes of structural elements are varied repeatedly to find-out the best locations of mass, stiffness and strength centres to minimize the torsional irregularity ratio. The study is found to be very productive as the torsional irregularity ratio gets reduced very significantly.